PENGARUH KOMUNIKASI YANG BURUK TERHADAP PELAKSANAAN PROYEK KONSTRUKSI DI KOTA LAMONGAN - Wazir Maulana Albi (Universitas Muhammadiyah Surabaya, 2023)
Communication in a project is a key to success in project management. Errors or poor communication patterns in a project can have an impact on poor performance. This study aims to analyze the success of the project in terms of communication between project owners, contractors and consultants. The independent variables used in this study are communication in the use of costs, communication in the distribution of materials, and communication in designing schedules. The dependent variable used is communication to support project success. The sample in this study were 31 people who were directly involved in construction projects in the city of Lamongan. The results of the research that has been done is that all independent variables affect the dependent variable, and the most dominant variable that influences the dependent variable is communication in material distribution with a regression coefficient value of 0.618. Simultaneously there is a significant influence between the independent variables on the dependent variable with the results of the calculated F value compared to Ftable, so Fcount of calculated results is greater than Ftable (28.072> 2.960). Partially there is a significant influence between each independent variable forming the linear regression model individually on the dependent variable.